The Anti-diabetic Drug Gliquidone Modulates Lipopolysaccharide-Mediated Microglial Neuroinflammatory Responses by Inhibiting the NLRP3 Inflammasome - Kim, Jieun; Park, Jin-Hee; Shah, Keshvi; Mitchell, Scott John; Cho, Kwangwook; Hoe, Hyang-Sook (Frontiers in Aging Neuroscience, 2021)
The sulfonylurea drug gliquidone is FDA approved for the treatment of type 2 diabetes. Binding of gliquidone to ATP-sensitive potassium channels (SUR1, Kir6 subunit) in pancreatic β-cells increases insulin release to regulate blood glucose levels. Diabetes has been associated with increased levels of neuroinflammation, and therefore the potential effects of gliquidone on micro- and astroglial neuroinflammatory responses in the brain are of interest. Here, we found that gliquidone suppressed LPS-mediated microgliosis, microglial hypertrophy, and proinflammatory cytokine COX-2 and IL-6 levels in wild-type mice, with smaller effects on astrogliosis. Importantly, gliquidone downregulated the LPS-induced microglial NLRP3 inflammasome and peripheral inflammation in wild-type mice. An investigation of the molecular mechanism of the effects of gliquidone on LPS-stimulated proinflammatory responses showed that in BV2 microglial cells, gliquidone significantly decreased LPS-induced proinflammatory cytokine levels and inhibited ERK/STAT3/NF-κB phosphorylation by altering NLRP3 inflammasome activation. In primary astrocytes, gliquidone selectively affected LPS-mediated proinflammatory cytokine expression and decreased STAT3/NF-κB signaling in an NLRP3-independent manner. These results indicate that gliquidone differentially modulates LPS-induced microglial and astroglial neuroinflammation in BV2 microglial cells, primary astrocytes, and a model of neuroinflammatory disease.